The Cultural Values of Figure of Speech in the text Brahma Satisfies Lord Siva - Dewi Yulianti (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2021)
A discussion of figure of speech types and their meanings in the text Brahma Satisfies Lord Siva is presented in this paper. In addition to it, the Balinese cultural values, namely tri hita karana (three causes of happiness) conveyed by the figure of speech is presented as well. It will be useful not only for those who are engaged in text but also for puppeteers who love to use figure of speech in their performances. This topic needs to be researched because the text is a religious text which contains figure of speech with their cultural values. The meanings of the figure of speech cannot be separated from the theme of the text which is in line with the cultural values of the text.The data about the figure of speech is collected through library research and analyzed based on semantic theory and also on cultural elements since cultural elements are needed to reveal the cultural values of the text. In this study, the cultural elements are limited into 3 such as the custom and tradition, religion, and language. Theoretically, this paper will provide an insight of a religious text, specifically in relation with the cultural value contained in it. Practically, this paper can contribute to the world of education so that it will help people to grow their understanding of religious text and Balinese cultural values.